Online fluorescence anisotropy immunoassay for monitoring insulin secretion from islets of Langerhans. Issue 1 (4th November 2016) - Schrell, Adrian M.; Mukhitov, Nikita; Yi, Lian; Adablah, Joel E.; Menezes, Joshua; Roper, Michael G.
Abstract : Insulin secretion from islets of Langerhans is a dynamic process that is essential for maintaining glucose homeostasis. Abstract : Insulin secretion from islets of Langerhans is a dynamic process that is essential for maintaining glucose homeostasis. The ability to measure dynamic changes in insulin levels upon glucose stimulation from single islets will allow testing of therapeutics and investigating mechanisms of defective secretion observed in metabolic diseases. Most approaches to date for measurement of rapid changes in insulin levels rely on separations, making the assays difficult to translate to non-specialist laboratories. To enable rapid measurements of secretion dynamics from a single islet in a manner that will be more suitable for transfer to non-specialized laboratories, a microfluidic online fluorescence anisotropy immunoassay was developed. A single islet was housed inside a microfluidic chamber and stimulated with varying glucose levels from a gravity-based perfusion system. The total effluent of the islet chamber containing the islet secretions was mixed with gravity-driven solutions of insulin antibody and Cy5-labeled insulin. After mixing was complete, a linearly polarized 635 nm laser was used to excite the immunoassay mixture and the emission was split into parallel and perpendicular components for determination of anisotropy. Key factors for reproducible anisotropy measurements, including temperature homogeneity and flow rate stability were optimized, which resulted in a 4 nM limit of detection for insulin with <1% RSD of anisotropy values. The capability of this system for measuring insulin secretion from single islets was shown by stimulating an islet with varying glucose levels. As the entire analysis is performed optically, this system should be readily transferable to other laboratories.